Study of Antibiotics Residue on Poultry Produscts in Indonesia - Etikaningrum, Etikaningrum; Iwantoro, S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
One of the popular livestock product in Indonesia is chicken meat. Poultry farm use antibiotics to treatment of poultry disease, therapy, supportive or prevention and food additive to improve chicken performance. However, use antibiotic not suitable with regulation can be residues to poultry product. The residues can affect various disease such as allergy, toxicity, affecting intestinal flora, immune response, resistance to microorganisms and etc. The purpose of this study is to know about how many case of residue antibiotic in indonesia and improve awareness poultry farmers and consumer about the dangerous of antibiotics in poultry product. In 1993- 2004 case about antibiotics residues in poultry product in indonesia was found. The range of antibiotic residues found in chicken meat is 8% -70%. The case antibiotics residues in poultry product found in some area with different various types antibiotics. Antibiotics residues case in 2011-2016 in Indonesia was decrease, even some research not found the antibiotics residues case in poultry product. But, another researcher found antibiotics residues from tetraciclyn in poultry product with small concentration (4,1% and 4,17%). While, antibiotics residues case in chicken liver is more than antibiotics residues case in chicken meat (4.17% -83.3%).